Transient heparin-induced platelet activation linked to generation of platelet 12-lipoxygenase - McMahon, Greg S.; Jones, Chris I.; Hayes, Paul D.; Naylor, A. Ross; Goodall, Alison H. (Thrombosis and Haemostasis, 2013)
Previously we demonstrated that heparin administration during carotid endarterectomy (CEA) caused a marked, but transient increase in platelet aggregation to arachidonic acid (AA) and adenosine diphosphate (ADP), despite effective platelet cyclo-oxygenase-1 (COX-1) inhibition with aspirin. Here we investigated the metabolism of AA via platelet 12-lipoxygenase (12-LOX) as a possible mediator of the observed transient aspirin resistance, and compared the effects of unfractionated (UFH) and low-molecular-weight (LMWH) heparin. A total of 43 aspirinated patients undergoing CEA were randomised in the trial to 5,000 IU UFH (n=22) or 2,500 IU LMWH (dalteparin, n=21). Platelet aggregation to AA (4×10–3) and ADP (3×10–6) was determined, and the products of the COX-1 and 12-LOX pathways; thromboxane B2 (TXB2) and 12-hydroxyeicosatretraenoic acid (12-HETE) were measured in plasma, and in material released from aggregating platelets. Aggregation to AA increased significantly (∼10-fold) following heparinisation (p<0.0001), irrespective of heparin type (p=0.33). Significant, but smaller (∼2-fold) increases in aggregation to ADP were also seen, which were significantly lower in the platelets of patients randomised to LMWH (p<0.0001). Plasma levels of TxB2 did not rise following heparinisation (p=0.93), but 12-HETE increased significantly in the patients’ plasma, and released from platelets stimulated in vitro with ADP, with both heparin types (p<0.0001). The magnitude of aggregation to ADP correlated with 12-HETE generation (p=0.03). Heparin administration during CEA generates AA that is metabolised to 12-HETE via the 12-LOX pathway, possibly explaining the phenomenon of transient heparin-induced platelet activation. LMWH has less effect on aggregation and 12-HETE generation than UFH when the platelets are stimulated with ADP.
Keywords: Platelets; heparin; aspirin; 12-lipoxygenase; carotid endarterectomy